Battles of the ancient world, 1285 BC-AD 451 : from Kadesh to Catalaunian Field - DeVries, Kelly, 1956- (London : Amber Books, 2011)
Introduces 20 key battles from Europe and the Middle East in a 2000-year period defined by the great empires of the Ancient world.
Includes bibliography (p. 216-217) and index.
Keywords: Kadesh, Battle of, Kadesh, ca. 1300 B.C.; Cannae, Battle of, Italy, 216 B.C.; Punic War, 2nd, 218-201 B.C.; Macedonian War, 3rd, 171-168 B.C.; Marathon, Battle of, Greece, 490 B.C.; Salamis, Battle of, Greece, 480 B.C.; Greece -- History -- Persian Wars, 500-449 B.C. -- Campaigns; Greece -- History -- Spartan and Theban Supremacies, 404-362 B.C.; Iran -- History -- Macedonian Conquest, 334-325 B.C.; Rome (Italy) -- History -- Empire, 30 B.C.-476 A.D.; Egypt -- History -- To 332 B.C.; Germany -- History -- To 843.; Gaul -- History -- 58 B.C.-511 A.D.